2005
DOI: 10.1523/jneurosci.3073-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Modulation of Vibrissal Receptive Fields in Trigeminal Nuclei

Abstract: In sensory systems, it is usually considered that mesopontine cholinergic neurons exert their modulatory action in the thalamus by enhancing the relay of sensory messages during states of neural network desynchronization. Here, we report a projection heretofore unknown of these cholinergic cells to the interpolar division of the brainstem trigeminal complex in rats. After FluoroGold injection in the interpolar nucleus, a number of retrogradely labeled cells were found bilaterally in the pedunculopontine tegmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…Together, these factors provide a reasonable explanation for the gradients of response magnitude and onset latency observed in projection cells. They are also consistent with the observation that the receptive field size of projection cells depends strongly on a muscarinic modulation that produces a twofold increase in input resistance, so that scopolamine administration in vivo results in a marked shrinkage of receptive field size (Timofeeva et al, 2005); however, these factors alone do not explain why response magnitude depends on the direction of vibrissa displacement.…”
Section: Receptive Field Synthesissupporting
confidence: 87%
“…Together, these factors provide a reasonable explanation for the gradients of response magnitude and onset latency observed in projection cells. They are also consistent with the observation that the receptive field size of projection cells depends strongly on a muscarinic modulation that produces a twofold increase in input resistance, so that scopolamine administration in vivo results in a marked shrinkage of receptive field size (Timofeeva et al, 2005); however, these factors alone do not explain why response magnitude depends on the direction of vibrissa displacement.…”
Section: Receptive Field Synthesissupporting
confidence: 87%
“…Similarly, the CRH neurons of the BN connect with the RAS to stimulate arousal in response to interoceptive input (38,39). The NO/acetylcholine neurons of the RAS connect back to proprioceptive nuclei such as the spinal trigeminal nucleus in the medulla, where cholinergic stimulation increases the excitability of glutamatergic projection neurons (42). Some of these neurons then connect to the thalamus as part of conscious proprioception and others contribute to the cerebellar unconscious proprioceptive network (34).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that some behavioral tasks require input from multiple whiskers (Krupa et al 2001), while others can be performed with only one intact whisker (Knutsen et al 2006). Inhibitory, neuromodulatory, and corticofugal projections have been shown to influence sensory stimulus encoding (Simons and Carvell 1989;Jacquin et al 1990;Lee et al 1994a, b;Fanselow and Nicolelis 1999;Castro-Alamancos 2002;Temereanca and Simons 2004;Timofeeva et al 2005;Higley and Contreras 2007;Li and Ebner 2007;Urbain and Deschenes 2007a,b;Furuta et al 2008;Lee et al 2008;Furuta et al 2010). All of these processes are potential contributors to this systemic flexibility.…”
Section: Discussionmentioning
confidence: 99%